Numerical Analysis of the Flame-Arresting Performance of a Pipeline Flame Arrester - Huang, Qian; Liao, Rui; Xiao, Jiangtao; Tian, Yuan; Huang, Huirong; Long, Xueyuan (Processes, 2025)
This research aims to create a numerical model for analyzing the flame propagation and quenching mechanisms of a pipeline flame arrester. Based on fundamental theories of flame propagation and quenching, a numerical model is established and solved using Ansys Workbench. The model accuracy is verified by comparing numerical results with experimental data. The verified model enables detailed flow field analysis. Using this validated model, a detailed flow field analysis is conducted. The temperature field and chemical reaction rate distribution under practical working conditions are analyzed. A method for determining the quenching length is established. The effects of flame arrester porosity, flame arrester core thickness, inlet flame velocity, and flame arrester length on the quenching length are analyzed. The Box-Behnken response surface method is applied to predict the quenching length. This approach produces an accurate prediction equation. These results can help improve flame arrester design and strengthen safety performance.